2019
DOI: 10.3390/su11030721
|View full text |Cite
|
Sign up to set email alerts
|

Producers’ and Consumers’ Perception of the Sustainability of Short Food Supply Chains: The Case of Parmigiano Reggiano PDO

Abstract: Recent literature has highlighted the importance of testing the sustainability performances of supply chains. Nevertheless, this field of research is still in its early stages, in particular with reference to short food supply chains (SFSCs). This research analyzed producers’ and consumers’ perception of the economic, social and environmental sustainability of two SFSCs of a specific quality of cheese (Parmigiano Reggiano PDO) placed in two different contexts: the first is a rural area in the Appennino Tosco-E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
70
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 49 publications
3
70
0
3
Order By: Relevance
“…Contrary to some perceptions and policy discourses, locally produced food does not always represent the most environmentally friendly option and close empirical assessments are correspondingly necessary (e.g., [7,8]). Although there is increasing interest in short food supply chains in policy and research domains, most studies adopt a descriptive case study approach, with only a few studies evaluating the effects of the food supply chain on farmer and consumer perceptions, behaviors or the circumstances with experimental or quasi-experimental designs [4,[9][10][11][12][13][14][15][16][17]. More comparative studies are needed to estimate the effects of such initiatives, but there are many technical difficulties in assessing the effects of ongoing practices and robust evaluation studies are too costly in terms of time and resources.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Contrary to some perceptions and policy discourses, locally produced food does not always represent the most environmentally friendly option and close empirical assessments are correspondingly necessary (e.g., [7,8]). Although there is increasing interest in short food supply chains in policy and research domains, most studies adopt a descriptive case study approach, with only a few studies evaluating the effects of the food supply chain on farmer and consumer perceptions, behaviors or the circumstances with experimental or quasi-experimental designs [4,[9][10][11][12][13][14][15][16][17]. More comparative studies are needed to estimate the effects of such initiatives, but there are many technical difficulties in assessing the effects of ongoing practices and robust evaluation studies are too costly in terms of time and resources.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature reviewed, we found that articles focused mostly on assessments of localized programs such as farmers' markets, cooperatives or selling schemes [9][10][11][12][13][14][15][16][17]. These publications tend to describe the initiatives and address impacts based on the perceptions of the experience of their users, collected by interviews and surveys.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the popularity and significance of short food supply chains as alternatives [22] and possibilities to solve some problems related to food safety issues [23] and conventional distribution systems has been constantly growing. This process allows the development of partner relations between producers and consumers and promotes the implementation of sustainable development principles [24][25][26].…”
Section: Discussionmentioning
confidence: 99%